Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Fantasies of femininity: Reframing the boundaries of sex - Ussher, Jane M. (Rutgers University Press, 1997)
In Fantasies of Femininity, Jane Ussher focuses on unraveling the contradictory visions of feminine sexuality: the fact that representations of the definition of woman seethe with sexuality yet for centuries women have been condemned for exploring their own sexual desires. In her quest for the sources of feminine representation, Ussher interviewed dozens of women - as well as some men - and combed popular media - from Seventeen to Cosmopolitan and Dallas to Donahue - to identify what shapes women's symbolic images of sex and femininity. Ussher argues that women have effectively resisted and subverted these archetypal fantasies of femininity, and in the process of so doing, reframed the very boundaries of sex. In this way, she exposes as myth much of what we think we know about "woman" and about "sex."
Keywords: approches et analyses; cours; discipline; fem1000; inégalités; premier cycle; psychologie; sciences humaines; sexualité; sexualité féminine; stéréotypes; systèmes d'oppressions; thématiques; études culturelles

Garçons et filles : stéréotypes et réussite scolaire - Bouchard, Pierrette; St-Amant, Jean-Claude (Itinéraires féministes, 1996)
En vue de comprendre les mécanismes menant à la réussite scolaire au secondaire, la recherche se penche sur les modèles d'identification qu'offrent, aux garçons et aux filles, les stéréotypes sexuels. Elle vérifie, à l'aide d'une enquête auprès de 24 écoles secondaires québécoises, le degré d'adhésion aux stéréotypes et son influence sur les rapports entretenus avec l'école. Elle démontre qu'un meilleur rendement scolaire passe par un affranchissement des modèles de sexe. Questionnaire en annexe.
Keywords: approches et analyses; cours; discipline; premier cycle; psy4910; psychologie; recherche quantitative; sciences humaines; sexisme; stéréotypes de genre; systèmes d'oppressions; systèmes éducatifs; études de genres